2007
DOI: 10.1007/s00270-007-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

Dose Perturbation Caused by Stents: Experiments with a Model 90Sr/90Y Source

Abstract: The results provide a warning that clinical indications for in-stent radiation therapy must always be confronted with another aspect of the patient's history: the kind of implanted stent. Intravascular brachytherapy using pure beta sources may be recommended only for patients "wearing" light, thin-strut stents. The presence of thick-strut stents is a contraindication for this modality, due to excessive dose perturbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Against this hypothesis, Nath and Yue 9 tested the shielding effect of metallic encapsulation and radiographic contrast agents for catheter-based intravascular brachytherapy, by using both photonand ␤-emitting radionuclides, and showed that if the shielding effect was present when low-energy photon emitters were used, it became minimal for high-energy photons (range of energy used in radiation therapy). Wilczek et al 10 tested the dose perturbation induced by different stents in brachytherapy and noticed that the shielding effect exists and depends on the strut thickness and mesh attenuation rather than on the atomic number of the metal. Shtraus et al 11 found that the measured attenuation of Onyx placed in a bottle was 3% higher than the attenuation of water.…”
Section: Discussionmentioning
confidence: 99%
“…Against this hypothesis, Nath and Yue 9 tested the shielding effect of metallic encapsulation and radiographic contrast agents for catheter-based intravascular brachytherapy, by using both photonand ␤-emitting radionuclides, and showed that if the shielding effect was present when low-energy photon emitters were used, it became minimal for high-energy photons (range of energy used in radiation therapy). Wilczek et al 10 tested the dose perturbation induced by different stents in brachytherapy and noticed that the shielding effect exists and depends on the strut thickness and mesh attenuation rather than on the atomic number of the metal. Shtraus et al 11 found that the measured attenuation of Onyx placed in a bottle was 3% higher than the attenuation of water.…”
Section: Discussionmentioning
confidence: 99%
“…54 The shield effect is the subject of controversy, but several reports suggest that embolic material partially decreases the delivered dose. 4,12,42,66 With the introduction of Onyx (ev3), clinicians believed that these disadvantages of prior embolic materials would be significantly reduced. First of all, it is well known that embolization with a liquid embolic agent such as Onyx has a lower recanalization rate than embolization with particles.…”
Section: Discussionmentioning
confidence: 99%